DIGITAL REVOLUTION IN SUPPLY CHAIN FINANCE: OVERCOMING CHALLENGES AND BUILDING INNOVATIVE STRATEGIES - Supriadi, Iman; Maghfiroh, Rahma Ulfa; Abadi, Rukhul (Klabat Accounting Review, 2024)
This research aims to analyze the impact of digital technology implementation in Supply Chain Finance, identify challenges in its implementation, and explore development and innovation strategies to optimize the process. This research uses a qualitative approach with literature studies and case studies. Data and information were collected through journals, articles, and reports related to digitalization in Supply Chain Finance. Analysis was conducted through a descriptive approach to understand and interpret the data. The results showed that digitization improves operational efficiency in Supply Chain Finance through process automation and data-driven decision-making. However, there are challenges, including significant initial investments and data security issues. Technologies such as AI, Machine Learning, blockchain, and big data contribute significantly to Supply Chain efficiency and resilience. This research presents insights into the application of digital technologies in Supply Chain Finance, providing insights into the challenges faced and strategies that can be implemented to overcome these challenges. This research contributes to practitioners' and academics' understanding of the potential and limitations of digital technology in the context of supply chain finance. Keywords: Digitalization, Supply Chain Finance, Blockchain, Artificial Intelligence, Big Data Penelitian ini bertujuan untuk menganalisis dampak penerapan teknologi digital dalam Supply Chain Finance, mengidentifikasi tantangan dalam implementasinya, dan mengeksplorasi strategi pengembangan serta inovasi untuk mengoptimalkan proses tersebut. Penelitian ini menggunakan pendekatan kualitatif dengan studi literatur dan studi kasus. Data dan informasi dikumpulkan melalui jurnal, artikel, dan laporan terkait digitalisasi dalam Supply Chain Finance. Analisis dilakukan melalui pendekatan deskriptif untuk memahami dan menginterpretasikan data yang ada. Hasil penelitian menunjukkan bahwa digitalisasi meningkatkan efisiensi operasional dalam Supply Chain Finance melalui otomatisasi proses dan pengambilan keputusan berbasis data. Namun, terdapat tantangan, termasuk investasi awal yang besar dan isu keamanan data. Teknologi seperti AI, Machine Learning, Blockchain, dan big data berkontribusi signifikan dalam efisiensi dan resiliensi Supply Chain. Penelitian ini menyajikan wawasan mengenai penerapan teknologi digital dalam Supply Chain Finance, memberikan pandangan mengenai tantangan yang dihadapi serta strategi yang dapat diterapkan untuk mengatasi tantangan tersebut. Penelitian ini memberikan kontribusi bagi praktisi dan akademisi dalam memahami potensi dan batasan teknologi digital dalam konteks Supply Chain Finance. Kata kunci: Digitalisasi, Supply Chain Finance, Blockchain, Kecerdasan Buatan, Big Data